An Empirical Relationship between Entrepreneurship and FDI. A Note. - Miltiades N. Georgiou (Max Planck Institute of Economics, 2006)
In the present note an effort will be made for a contribution to economic theory by estimating an econometric relationship between the foreign direct investment [FDI] and total economys entrepreneurship reward [rEM]. This note is based mainly on the next two papers. First, it will be based on the discussion paper Understanding the Role of Entrepreneurship for Economic Growth. by Martin Carree and Roy Thurik, MPIoE, #2005, in which the authors show the importance of entrepreneurship to adapt to new technology, to develop capacity and reach economies of scale. Second, it will be based on the discussion paper Does Entrepreneurship Create Enough Jobs in Europe? A Note. by Miltiades N. Georgiou, MPIoE, #0806, in which entrepreneurship reward [rEM] is measurable and consequently can be related with the other measurable economic variables like the [FDI]. Hence, in the present note a relationship between [FDI] and [rEM] can be numerically estimated. More specifically, it will be pointed out with panel data econometric analysis that in all Western European Countries and the United States [FDI] is positively related with [rEM], and that decisions about [FDI] are mainly affected by [rEM].
Keywords: 330